Pengembangan Metode Pembuatan Molding Injeksi Plastik dari Serbuk Komposit - Suryo Darmo (Faculty of Engineering, Universitas Gadjah Mada, 2015)
Aluminium-particulate glass matrices composites generally use the pressure in the making of green parts/green specimens before heating at sintering temperature.The purpose of this research is to develop the glass composites that it can be used as a material for indirect layer manufacturing, especially used for making plastic injection mold/insert mold. To achieve these goals, the flexural strength and dimensional errors were studied.Starting materials consist of the mixture of glass powders, aluminium powders, and acrylic powders in the volume ratio of 1 : 1 : 1. The glass powders and aluminium powders wererecovered from waste materials. The size of acrylics and glass particles was lower than 0.074 mm and aluminium particles size was lower than 0.297 mm respectively. Green specimens were made by using indirect layer manufacturing processes, while sintered specimens obtained by heating the green specimens in a furnace at a temperature of 700°C for 1 hour. Finished specimens were made by impregnation process of sintered specimens using epoxy resin.The bending strength of green specimens, sintered specimens, and finished specimens is 20 kg/cm2, 80 kg/cm2, and 170 kg/cm2 respectively. Maximum dimensional error of green specimens and sintered specimens is 50% and 40% respectively. Insert mold made by indirect layer manufacturing is broken after producing as many as 120 pieces of plastic products.Keywords: glass matrix composite, insert mold, dimensional error, bending strength.